2013
DOI: 10.1504/ijil.2013.052897
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effects of learning style in business statistics

Abstract: Business majors at AACSB accredited schools are required to take undergraduate statistics. Much research has been done with various learning style models for students enrolled in core business courses such as accounting, management, economics, and finance. However, the author has found no research that attempts to quantify the effects of learning style for students in business statistics. This study demonstrates that learning style as measured using the VARK model has significant effects on numerous variables … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Results indicated that lecturer competence, teaching methods and quality of learning materials had a positive influence on business students' academic achievements in quantitative business courses. Stevens (2013) measured the effect of learning style on several variables for students in undergraduate business statistics. The author demonstrated that learning style, as measured using the VARK (Visual, Aural, Read-write or Kinesthetic) model, had significant effects on a number of variables such as academic success, student perceptions of course and instructor and academic major.…”
mentioning
confidence: 99%
“…Results indicated that lecturer competence, teaching methods and quality of learning materials had a positive influence on business students' academic achievements in quantitative business courses. Stevens (2013) measured the effect of learning style on several variables for students in undergraduate business statistics. The author demonstrated that learning style, as measured using the VARK (Visual, Aural, Read-write or Kinesthetic) model, had significant effects on a number of variables such as academic success, student perceptions of course and instructor and academic major.…”
mentioning
confidence: 99%
“…Three sets of questions were utilised to obtain the data for this analysis. The three sets of questions include a group to determine student perceptions of course and instructor [as utilised by Stevens (2013)], a group to determine student perceptions of the usefulness and effectiveness of clickers, and a group of demographic questions. The first group of questions mentioned above is taken from the university's 'SEI', and assesses student opinions in five areas: instructor's verbal communication skills, instructor's written communication skills, effectiveness of teaching methods for the course, whether the student would recommend the instructor, and whether the student would recommend the course.…”
Section: Methodsmentioning
confidence: 99%
“…Common effect size measurements include (Pearson's) correlation coefficient (denoted 'r'), η 2 ['eta-squared': see Burns and Burns (2008)], and the effect size index, f, proposed by Cohen (1988). Stevens (2013) uses both r and η 2 in related research about the size of the effect of learning style on academic success and perceptions of course and instructor. The authors, therefore, utilise these same effect size measures in the present research regarding clicker effectiveness.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nuzhat, Salem, Hamdan, and Ashour (2013) in their study among medical students in Saudi Arabia found that students with multimodal learning preference achieved comparatively better results than their unimodal counterparts in the same course. Other than that, Stevens (2013) has investigated the learning styles effects on few variables among undergraduate business statistics students. He found that the preferences significantly affected the variables which included academic success.…”
Section: Literature Reviewmentioning
confidence: 99%